Intraurban Near-Water Areas and Their Role in Distribution of Ticks (Acari, Ixodidae) in Megalopolis the Example of Kyiv - Небогаткин, И.В. (Вестник зоологии, 2012)
In 2002—2009, we studied 12 islands within the city of Kyiv, and found four indigenous species of ticks (Dermacentor reticulatus Fabricius, 1794; Ixodes ricinus Linnaeus, 1758; I. apronophorus Schulze, 1924; Rhipicephalus rossicus Jakimov et Kohl-Jakimova, 1911) and one invasive species (Hyalomma marginatum Koch, 1844). For A—E-gradient, established by man’s impact degree, we revealed atypical distribution of species: their majority is noted in two pole areas – where the man impact is maximum and minimum. The investigated near-water areas are a kind of survival areas and sources of ixodides diversity in megalopolis.